QOLP-08. A NEURO-ONCOLOGY CAREGIVER SUPPORT GROUP, AN EFFECTIVE WAY TO PROVIDE EMOTIONAL SUPPORT FOR CAREGIVERS. (5th November 2018) - Page, Margaretta; Rossi, Rosemary; Woodall, Marielle; Chang, Susan
Abstract: BACKGROUND: Brain tumor support groups provide education and emotional support to patients and families dealing with a brain tumor diagnosis. These groups are beneficial, but at times caregivers report that they must hold back and not speak their truth/reality for fear of hurting the patients feelings. A neuro-oncology caregiver support group is one easy and economical way to provide caregivers with emotional support and foster resilience. A regular attendee reminds us that caregivers need a place to not have to be strong, to not have to be everything all the time, and to be around people that understand. METHOD: A UCSF neuro-oncology caregiver support group is led by a social worker and neuro-oncology RN once a month. The group provides caregivers a safe space to share feelings and focus on their experience of being a caregiver and coping with the emotional aspects of caring for someone with a brain tumor. Participants are invited to acknowledge and share the complicated emotions that they experience. Themes are documented and participants surveyed annually. RESULTS: In 2017–2018, 30 caregivers attended the monthly meetings with an average of 10 attendees. 6 attended all meetings in the last year. Common themes include sorrow, anger, ambiguous loss, guilt, and ways to find joy and humor. Annual survey results demonstrate a mix of male and females, some who travel over 75 miles to be at the meeting. 93% of those responding reported benefit from the opportunity to normalize feelings and learn from each other. 93% reported that the group reduced their sense of isolation and 100% rated the group as beneficial and would recommend the group to others. CONCLUSION: A neuro-oncology caregiver specific support group is a feasible and economic way to assist caregivers in normalizing complicated emotions, connecting with similar others, and may foster resilience.